Reviewing the Literature on Staff Misconduct and Specific Responsivity - Oleksy, Ernest M (2019)
Incarceration is a trying time for inmates as they are punished for crimes they committed while free in society. Beyond the legitimate punishment of being imprisoned, inmates may face illegitimate punishment at the hands of prison staff, ranging from ridicule to physical and sexual violence. Apart from the obvious corruption and immorality involved in staff misconduct, such deviance can also result in a dampened responsivity to reentry programming efforts that strive to keep inmates out of prison. In this literature review, I investigate, summarize, and synthesize the corpus that is relevant to how staff misconduct can be a negative specific responsivity factor